Determination of the genetically-significant dose from diagnostic radiology for the South African population, 1990-1991 - Maree, Gert Johannes (Division of Medical Physics, 2017)
The International Commission on Radiological Protection (ICRP) determines the policy regarding radiation safety internationally. To the ICRP, hereditary changes as a result of either high or low doses, are of a major concern. The SA Forum for Radiation Protection recommended that a research project to determine the genetically-significant dose (GSD) for the South African population should be done as such a project has never been undertaken to date. This term was at first defined by UNSCEAR in 1958. The National Radiological Protection Board derived a formula from this definition as shown in the NRPB Report, NRPB-R106 (1980). This formula was implemented in the project. It combines the frequency of radiological examinations obtained during the country-wide survey and estimates of gonadal doses for different examination types, together with population and child expectancy data. New procedures, techniques and data processing that were relevant to this project had to be developed because the available information and conditions are unique to South Africa. The task was set to find a model in order to draw the best representative sample of the population and it was determined in a unique way, namely the so-called Dollar Unit Sampling method. A sample of 27 institutions out of a possible 292 (9%) was drawn in comparison, e.g., with the 8% of France and 8% in Great Britain. It was necessary to rely mainly on the calculation of gonad doses due to a shortage of manpower, contrary to other countries that were able to physically measure doses. Information obtained in the survey was used in this regard. The "RADCOMP Entrance Skin Exposure Software Program " of Nuclear Associates was used to produce parametric Free Air Exposure tables based on doses from Table B.3, NCRP Report No. 102. After the skin entrance doses were calculated, it was possible to calculate the gonad doses. A computer program was obtained from the Food and Drug Administration in the USA for this purpose. Data analysis was performed by means of the software package Microsoft Excel version 4.0. The above-mentioned formula was used in order to obtain the final results. The GSD for the total SA-population was calculated as 94.6 μGy. The breakdown of the GSD for the various South African race groups was Asian - 229.0 μGy, Black - 66.5 μGy, Coloured - 112.2 μGy and White - 463.4 μGy.